POWERFULL PUBLIC SPEAKING (Peran Aspek Komunikasi Vebral dan Non-Verbal dalam Menunjang Efektifitas Penyampaian Pesan Public Speaking) - Enung Nurhayati (ADISAM PUBLISHER, 2025)
Public speaking is the act of orally presenting in front of a public with the aim of conveying ideas/thoughts, information or certain messages using the right strategy and techniques. Public speaking is also an art and a science, it involves the ability to communicate clearly, easily understood and attract the attention of the audience. As a form of art, public speaking combines the power of words with the ability to influence and inspire an audience using a persuasive or even provocative style of language. It is more than just delivering a speech; it is about the art of connecting with audience emotionally as well as intellectually , conveying a message, and making an impact accordance with the speaker's goal. As a science, public speaking related to effective communication strategies and techniques. Great communication doesn’t just happen, it has to be thought and prepared, structured and delivered with good techniques. To ensure an effective communication, speakers can developing and implementing verbal and non-verbal language skills. Verbal aspect involves everything related to the words used by a speaker. Among other things, it includes the selection of appropriate words/diction, proper sentence structure, the ability to express clear and logical thoughts, and message delivery techniques. The technique of delivering a message here is related to vocal/sound, including; vocal volume, intonation, accentuation and rhythm to convey the message clearly and captivate the audience's ears. Nonverbal aspect related to the way of delivering the message, includes the use of body language, eye contact, facial expressions, and vocal intonation. By developing skills of verbal and non-verbal aspects in public speaking practice and applying the right techniques delivery, a speaker can convey a message more powerfull and also impactfull